The Effect Of Role-Playing Learning Model On The Speaking Skills Of Grade V Elementary School Students - Malinda, Maulidya Vini; Utama, Erdi Guna; Mulyani, Sri (International Journal of Research in Education, 2024)
This study aims to: 1) determine the effect of the role-playing learning model on the speaking skills of fifth grade students at SD Negeri 91 Singkawang; 2) knowing student responses in learning using the role-playing learning model for class VB SD Negeri 91 Singkawang. The research used was experimental research with a post test only control group design. The population in this study were fifth grade students at SD Negeri 91 Singkawang. The sample in this study were all fifth grade students at SD Negeri 91 Singkawang. The instruments in this study were speaking skill observation sheets and response questionnaires. Analysis of the first hypothesis data using t-test 2 samples and for the second hypothesis using descriptive statistics. The results showed that: 1) the role-playing learning model on students' speaking skills had an influence on Indonesian language subjects in class V at SD Negeri 91 Singkawang. and Ho is rejected; 2) positive student responses to the role-playing learning model as indicated by an average percentage of 97% in very good criteria. Based on the results of the study it was concluded that the role-playing learning model had an effect on Indonesian language learning because there was an expected increase in students' speaking skills